Assessing GHG mitigation and associated cost of French biofuel sector: Insights from a TIMES model. (15th October 2016) - Hugues, Paul; Assoumou, Edi; Maizi, Nadia
Abstract: Biofuel sector has been promoted in France for its environmental and societal advantages. However, controversial issues have emerged, especially on avoided GHG emissions, raising uncertainties regarding its future development. For an actor, investing in the appropriate pathway is yet not straightforward as resource availability, process efficiency and costs are uncertain and regulatory framework will impact future technological choices among current, second or third generation production processes. A better understanding of the dynamic of the whole industry is thus needed for informed policy. This paper relies on a TIMES prospective model of French bioenergy sector we developed that gives a dynamic technology allocation under constraints. We find that avoided emissions of the biofuel sector could range from 12 MtCO2eq for current regulatory context to 16 MtCO2eq for the future one. The higher is the mitigation level, the higher is the associated abatement cost: from less than 200 €/tCO2eq to more than 6000 €/tCO2eq as it would imply the development of advanced processes, such as algae biofuels. Externalities play a significant role on the technology merit order, and must also be considered for designing future incentive policy. Highlights: We describe a TIMES model of French bioenergy sector, focusing on biofuels. We assess GHG mitigation level and its associated cost under contrasting scenarios. Influence of learning curves and externalities on future biofuel mix are discussed. This paper provides insights for decision-making about French biofuel future.